A Study into the Efficiency of Indian Banking Sector and Its Determinants - Abhijit Sinha AND Tagar Lal Khan (Abhigyan, 2014)
In the backdrop of the recent sub-prime mortgage crisis that emerged in the US, affected all the countries across the globe. Specifically about our country, it is needless to mention that the impact on the banking industry was much less compared to the effect on other countries especially in real estate, tourism, information technology etc. Hence, the present study deserves to assess the efficiency of the banking industry by considering the large-sized public and private sector banks operating in India. For the purpose of our analysis, DEA is run over the period 2004-05 to 2011-12 for the top sixteen banks from the private and public sectors. The different aspects of bank efficiency such as Technical Efficiency, Pure Technical Efficiency and Scale Efficiency have been measured applying DEA. In the next part of the study, the Tobit regression is run in order to identify the exogenous factors contributing towards the efficiency of the banking sector, private as well as public sector